Filosofia selvagem: ensaio com o pensamento de Clarice Lispector - Pablo Vinícius Dias Siqueira (2019)
Wild philosophy is a philosophical adventure with the reflective thinking of Clarice Lispector. More than anything else, this paper is a wandering essay that comes into loving contact with the philosophical and the literary life of Lispector. The term wild here refers mainly to two things. The way in which Lispector's thinking is shaped and also the way this essay presents itself: both are insubordinate, open and provocative. Just because it is wild, because it is an adventure and because it is philosophical, this essay does not submit to conventional norms, moorings and methodologies - unless it suits itself. In fact, play-of-think is the great method of research chosen to philosophize with the thinking of Clarice Lispector, in the genuine enconter that she set up between literature and philosophy. I am considering the reflective aspects of her work Discovering the world, The hour of the star, O mistério do coelho pensante, Para não esquecer e Quase de verdade (respectively, in wild english translation, The mystery of the thinking rabbit, Not to forget and Almost real), really flirting with The stream of life and A breath of life. Throughout the essay I thought about the moments in which Lispector, in partnership with life and the languages of life, dedicates himself to ethical and aesthetic issues and the political aspects of such issues, intrinsic to everyday life, but never hostage to it. I also investigated certain problems that Lispector herself creates and tries to solve by thinking, positioning herself philosophically before her own reflexive subjectivity. I also thought of the style, forms and certain expressions of thought as "intimate", "amateur", "fool", "play" and even "wild" that Lispector triggers as concepts of her own. Finally, Wild Philosophy is a fragmented, aforismatic, fictional, polemical, poetic essay that brings together so many philosophies from me and from Lispector, without hierarchies of content, without rigid explanations. All this allowed me to emphasize the literary, playful and daring trait that there are in the most challenging philosophical thoughts – as is the case of the thinking of Clarice Lispector.